Mechanism of miR-126 in hypoxia-reoxygenation-induced cardiomyocyte pyroptosis by regulating HMGB1 and NLRP3 inflammasome. (4th July 2022) - Fei, Ling; Zhang, Ning; Zhang, Jun
Abstract: Objective: Pyroptosis refers to the programmed cell death. This study evaluated the mechanism of miR-126 in hypoxia-reoxygenation (HR)-induced cardiomyocyte pyroptosis. Methods: The HR rat cardiomyocyte models were established. The cell viability, cytotoxicity, and levels of miR-126, pro-caspase-1 (p45), activated caspase-1 (p20/p10), caspase-11, gasdermin D (GSDMD), and GSDMD-N were detected. The cells were transfected with miR-126 mimics to verify the effect on rat cardiomyocyte pyroptosis, and added with HMGB1 inhibitor (Glycyrrhizin) or NLRP3 inhibitor (S3680) to explore the regulatory mechanisms on rat cardiomyocyte pyroptosis. The binding relationship of miR-126 and HMGB1 was explored. The regulatory effect of miR-126 and HMGB1 on HR-stimulated cardiomyocytes was verified through co-transfection with miR-126 mimics and pcDNA3.1-HMGB1. Results: HR treatment inhibited rat cardiomyocyte viability and increased cytotoxicity. After HR treatment, pro-caspase-1 (p45), activated caspase-1 (p20/p10), caspase-11, GSDMD, and GSDMD-N were elevated in rat cardiomyocytes, while miR-126 was evidently downregulated in rat cardiomyocytes. miR-126 overexpression, and inhibition of HMGB1 or NLRP3 partially reversed HR-induced rat cardiomyocyte cytotoxicity and pyroptosis. miR-126 targeted HMGB1 and HMGB1 overexpression partly reversed the inhibition of miR-126 overexpression on HR-induced cardiomyocyte pyroptosis. Conclusion: miR-126 inhibits HMGB1/NLRP3 activity and the caspase-1/11 activation and reduces the GSDMD-N cleaved from GSDMD, ultimately inhibiting HR-induced cardiomyocyte pyroptosis.